Anthrenus (s. str.) amandae (Coleoptera: Dermestidae): a new species from Mallorca, Spain - Holloway, Graham J. (Zootaxa, 2019)
A new species, Anthrenus amandae sp. nov., from Mallorca, Spain is described and illustrated. The species differs from likely confusion species on the basis of a combination of habitus morphometrics, antennal and male genitalia structure.